Palladium Complexes with the SC6F4H‐4 Ligand – Synthesis, Spectroscopy, and Structures1. Issue 25 (1st July 2013) - Lingen, Verena; Lüning, Anna; Strauß, Christian; Pantenburg, Ingo; Deacon, Glen B.; Klein, Axel; Meyer, Gerd
Abstract: The reaction of HSC6 F4 H‐4 or KSC6 F4 H‐4 with the palladium(II) complexes [(NN)PdCl2 ] [NN = 2, 2′‐bipyridine (bpy) or 1, 10‐phenanthroline (phen)] leads to the mononuclear palladium complexes [(NN)Pd(SC6 F4 H‐4)2 ] or [(NN)PdCl(SC6 F4 H‐4)], whereas the reaction with [(COD)PdCl2 ] (COD = 1, 5‐cyclooctadiene) results in the loss of COD and the formation of the oligonuclear species [Pd(SC6 F4 H‐4)2 ] m . For NN = phen, the compound [(phen)2 K(μ‐phen)2 K(phen)2 ][(4‐HC6 F4 S)2 Pd(μ‐SC6 F4 H‐4)2 Pd(SC6 F4 H‐4)2 ] containing a homoleptic dimeric dianionic Pd complex was also obtained. The reaction of KSC6 F4 H‐4 with PdCl2 yielded K2 [Pd(SC6 F4 H‐4)4 ]. The new compounds were analysed and characterised by single‐crystal XRD, 1 H and 19 F NMR spectroscopy and IR spectroscopy. The UV/Vis absorption spectroscopy and electrochemistry of [(bpy)Pd(SC6 F4 H‐4)2 ] have been investigated and are compared to those of the related Pt derivative [(bpy)Pt(SC6 F5 )2 ]. Abstract : Preparation routes to palladium(II) complexes with the SC6 F4 H‐4 ligand and their structures and spectroscopy have been studied by single‐crystal XRD, multinuclear NMR spectroscopy, UV/Vis absorption spectroscopy, and electrochemistry.